2021
DOI: 10.1021/acs.molpharmaceut.1c00323
|View full text |Cite
|
Sign up to set email alerts
|

PARP-Targeted Auger Therapy in p53 Mutant Colon Cancer Xenograft Mouse Models

Abstract: Despite Auger electrons being highly appealing due to their short-range and high linear energy transfer to surrounding tissues, the progress in the field has been limited due to the challenge in delivering a therapeutic dose within the close proximity of cancer cell’s DNA. Here, we demonstrate that the PARP inhibitor 123I-MAPi is a viable agent for the systemic administration and treatment of p53 mutant cancers. Significantly, minimal off-site toxicity was observed in mice administered with up to 74 MBq of 127… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…The in vivo study with [ 123 I]MAPi showed promising therapeutic efficacy and survival advantage upon intra-tumoural delivery in glioblastoma models. A recent study with systemic [ 123 I]MAPi administration presented its high therapeutic efficacy in preclinical model of colorectal cancer with p53 deficiency [ 14 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…The in vivo study with [ 123 I]MAPi showed promising therapeutic efficacy and survival advantage upon intra-tumoural delivery in glioblastoma models. A recent study with systemic [ 123 I]MAPi administration presented its high therapeutic efficacy in preclinical model of colorectal cancer with p53 deficiency [ 14 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…Although biodistribution data showed that large fractions of [ 123 I]MAPi pass through the hepatobiliary system and uptake in several organs was higher than in tumors, only minimal systemic toxicity was observed in a toxicity study after GMP guidelines. It is hypothesized that during excretion, metabolism confines the agent to the perinuclear region of the cell and therefore puts it outside the range of an Auger-emitter to achieve significant damage upon cellular DNA [99]. Recently, another therapeutic study of an Auger-emitting PARPi, [ 125 I]PARPi-01 (isotopologue of [ 131 I]I2-PARPi from [57]), was published (Morgenroth Lab) [102].…”
Section: Rucaparib-like Radiotherapeuticsmentioning
confidence: 99%
“…While intratumoral injection might be considered for glioblastoma treatment clinically, for other tumor entities, it is not an option. Therefore, the therapeutic potential of [ 123 I]MAPi after systemic injection was evaluated in a colorectal cancer model comparing p53 +/+ to p53 −/− models [ 99 ]. In tumors, PARP1 expression is elevated in the nucleus, increasing the likelihood for the Auger-emitting isotope to induce DNA damage.…”
Section: Current Status Of Parp-targeted Radiotherapymentioning
confidence: 99%
See 2 more Smart Citations